Management by menu - Kotschevar, Lendal Henry; Withrow, Diane (New Jersey : John Wiley & Son, Inc., 2008)
[This book]presents the menu as the central influence on all foodservice functions. [It] outlines both the "big picture" behind a well-run foodservice operation, and the practical details of costing, planning, analyzing, purchasing and production, beverage management, promotion, and service. [This book is for] both students and working managers.
1. A look back at the foodservice industry -- 2. Profile of the modern foodservice industry -- 3. Planning a menu -- 4. Considerations and limits in menu planning -- 5. Cost control in menu planning -- 6. Menu pricing -- 7. Menu mechanics -- 8. Menu analysis -- 9. The beverage menu -- 10. Producing the menu -- 11. Service and the menu --12. The menu and the financial plan -- 13. Ethical leadership in restaurant management
Includes index.
Keywords: FOOD SERVICE MANAGEMENT